Industrial training report at SAP Wealth Advisory / Siti Nur Aisyah Ramlan - Ramlan, Siti Nur Aisyah (Universiti Teknologi MARA, Perlis, Faculty of Business and Management, 2021)
I have been doing my internship in SAP Wealth Advisory company which is an agency of Great Eastern which is one of the biggest insurance companies in Malaysia. From this internship, I was assigned to do sales and services regarding takaful product from Great Eastern Takaful Berhad. Before I started doing takaful services, company had provided the training class to expose about the takaful product and how it is works. I also attend the virtual training provided by Great Eastern Takaful which are Super Group Nationwide morning and night meeting, Million Income Program, and Kick Start. Through this program, I have learned a lot of things regarding takaful product, how to approach the prospect, how to handle the objection from the prospects, doing the posting through social media and so on. Before I officially become a takaful agent, I need to seat for a test which is Takaful Basic Examination (TBE) to be a legal agent. I passed the exam with B grade. For the daily routine, I have been exposed to do the ‘5352111’ routine which are make five new friends, doing three visits consist of open, present and follow up to the prospects, do five calls to people, two hours do hobby with friends, one hour reading about takaful or attend meeting, one hour learning or reading new things (other than takaful) and one hour doing paperwork. This routine taught me on how to be discipline doing my daily activities. I need to update the daily three visits report on WhatsApp group, and it will be discussed on the next day with the supervisor. The supervisor gives idea on how to approach the prospect effectively, handle the objection and so on. I am rarely contact my old friends from lower school, high school and diploma. It helps me to strengthen my relationship with people as well as improve my presentation about takaful products.